Supply Chain Risk Analysis on Vending Machine Products (Study Case in XYZ Company) - Puti Sinansari; Nugroho Priyo Negoro; Muhammad Muadz Abdillah (Institut Teknologi Sepuluh Nopember, 2021)
The development of business and technology ecosystems demands industry to always make adjustments. Supply chain changes become one that is certain to happen. This change process allows the company to manage and minimize risks. Therefore, it is necessary to apply good risk management to minimize the impact of risk. As one of the vending machine service companies in Indonesia, PT XYZ has a long supply chain, covering the production process, assembling, shipping and customer service. This research aims to identify risk events and risk agents and determine the priority of risk agents in the vending machine service company at PT XYZ. The design of this research uses the first stage House of Risk method to identify risk events and risk agents as well as determining the highest risk agent. Then the highest risk agent is ranked in Pareto diagram to determine risk agent priority. The prospect of this research will be an overview of the risks that may arise in the vending machine service company in Indonesia.